Expert perspectives on the prescription pattern of levocetirizine₊montelukast and fexofenadine₊montelukast for the management of allergic rhinitis in the Indian settings - S., Manjula; M., Krishna Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Studies have shown that oral antihistamines are considered as the gold-standard therapy for allergic rhinitis. However, there is dearth of studies among clinicians, so this study aimed to gather expert opinion on the prescribing pattern of levocetirizine₊montelukast and fexofenadine₊montelukast for managing AR in India. Methods: This cross-sectional study, conducted through a multi-response questionnaire comprising 24 questions, gathered insights from experts across diverse Indian settings. It explored perspectives on clinical observations, experiences, demographic profiles, treatment characteristics in AR, and the utilization of fexofenadine₊montelukast and levocetirizine₊montelukast for AR management in clinical practice. The data were analyzed through descriptive analysis. Results: Majority of clinicians (52%) preferred levocetirizine₊montelukast for AR, with half of them recommending a 2-week course. Additionally, 38% of clinicians noted its effectiveness in addressing all AR symptoms. Most clinicians agreed that levocetirizine and montelukast combination therapy was effective in improving nighttime nasal symptoms (74%) and nasal congestion (69%). Furthermore, majority of clinicians acknowledged that the combination offers both immediate (74%) and long-term (56%) relief from AR symptoms. Approximately 58% of the healthcare providers reported overall improvement across categories with fexofenadine₊montelukast, encompassing daytime nasal symptoms, nighttime nasal symptoms, and daytime eye symptoms. Conclusion: Clinicians recommended the combination of levocetirizine₊montelukast and fexofenadine₊montelukast to manage AR. Levocetirizine₊montelukast combination was preferred by clinicians for its efficacy in alleviating nighttime nasal symptoms and congestion. Fexofenadine₊montelukast combination was also endorsed for overall improvement across various symptoms.